2020
DOI: 10.1021/acs.jnatprod.0c00362
|View full text |Cite
|
Sign up to set email alerts
|

Strepimidazoles A–G from the Plant Endophytic Streptomyces sp. PKU-EA00015 with Inhibitory Activities against a Plant Pathogenic Fungus

Abstract: Seven new 4-acyl-2-aminoimidazoles, designated strepimidazoles A–G (1–7), were discovered from the endophytic Streptomyces sp. PKU-EA00015 isolated from Salvia miltiorrhiza Bunge, whose dry root “Danshen” is one of the most widely used traditional Chinese medicines. The resonance signals of the 2-aminoimidazole moiety in 1–7 were absent in the NMR spectra due to tautomerization, and the structures of 1–7 were identified after preparation of their acetylation products 1a–7a, respectively. Compounds 1–7 represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…SC-J0138 Diaporthichalasin D Cytotoxic activity Yang et al ( 2020a ) 44 Diaporthichalasin H 45 Nicotiana tabacum Rhizopycnis vagum KM095527 Rhizoperemophilane J Wang et al ( 2020 ) 46 Rhizoperemophilane N 47 Salvia miltiorrhiza Streptomyces sp. PKU-EA00015 Strepimidazoles A Antifungal activity Sun et al ( 2020 ) 48 Strepimidazoles B 49 Strepimidazoles C 50 Strepimidazoles D 51 Strepimidazoles E 52 Strepimidazoles F 53 Strepimidazoles G 54 Elaeis guineensis Jacq Streptomyces palmae CMU-AB204 ( Z )-5-(o-tolyl)pent-4-enoic acid Antifungal activity Sujarit et al ( 2020 ) 55 ( Z )-7-(o-tolyl)hept-6-enoic acid 56 ( Z )-11-(o-tolyl)undec-10-enoic acid Antibacterial activity 57 ( Z )-12-(o-tolyl)dodec-11-enoic acid 58 Aconitum vilmorinianum Penicillium variabile HM469398 Maz...…”
Section: Research Progress On the Biosynthesis Of Natural Products By Endophytic Fungimentioning
confidence: 99%
“…SC-J0138 Diaporthichalasin D Cytotoxic activity Yang et al ( 2020a ) 44 Diaporthichalasin H 45 Nicotiana tabacum Rhizopycnis vagum KM095527 Rhizoperemophilane J Wang et al ( 2020 ) 46 Rhizoperemophilane N 47 Salvia miltiorrhiza Streptomyces sp. PKU-EA00015 Strepimidazoles A Antifungal activity Sun et al ( 2020 ) 48 Strepimidazoles B 49 Strepimidazoles C 50 Strepimidazoles D 51 Strepimidazoles E 52 Strepimidazoles F 53 Strepimidazoles G 54 Elaeis guineensis Jacq Streptomyces palmae CMU-AB204 ( Z )-5-(o-tolyl)pent-4-enoic acid Antifungal activity Sujarit et al ( 2020 ) 55 ( Z )-7-(o-tolyl)hept-6-enoic acid 56 ( Z )-11-(o-tolyl)undec-10-enoic acid Antibacterial activity 57 ( Z )-12-(o-tolyl)dodec-11-enoic acid 58 Aconitum vilmorinianum Penicillium variabile HM469398 Maz...…”
Section: Research Progress On the Biosynthesis Of Natural Products By Endophytic Fungimentioning
confidence: 99%
“…Finally, perspectives are presented to better understand how the endophytic fungi area should evolve in the coming years. Although endophytic bacteria can also act to protect plants against biotic [ 25 , 26 , 27 ] and abiotic stresses, this is not the focus of this review.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 It has been suggested that some metabolites initially described from plants are either microbial products or mutual products of plants and endophytes. 4,5 This unique ecological origin makes endophytes a potential source for the discovery of novel products, such as polyketides, 6 macrolides, 7 alkaloids, 8,9 and terpenes, 10 for future drug development. 11,12 Cinnamoyl-containing natural products (CCNPs) featuring an ortho-substituted cinnamoyl group exhibit various bioactivities including antibacterial, antifungal, antitumor, and antiangiogenic.…”
mentioning
confidence: 99%
“…Endophytes have evolved many special enzymatic systems to adapt their symbioses with plants . The mutualism between endophytes and plants not only enables endophytes to utilize various nutrients or substances from plants but also stimulates endophytes to produce biologically active compounds. , It has been suggested that some metabolites initially described from plants are either microbial products or mutual products of plants and endophytes. , This unique ecological origin makes endophytes a potential source for the discovery of novel products, such as polyketides, macrolides, alkaloids, , and terpenes, for future drug development. , …”
mentioning
confidence: 99%